Evaluation of Patient Satisfaction with Tuberculosis Services in Southern Nigeria - Ugochukwu U. Onyeonoro; Joseph N. Chukwu; Charles C. Nwafor; Anthony O. Meka; Babatunde I. Omotowo; Nelson O. Madichie; Chidubem Ogbudebe; Joy N. Ikebudu; Daniel C. Oshi; Ngozi Ekeke; Nsirimobu I. Paul; Chukwuma B. Duru (SAGE Publishing, 2015)
Objective Knowing tuberculosis (TB) patients' satisfaction enables TB program managers to identify gaps in service delivery and institute measures to address them. This study is aimed at evaluating patients' satisfaction with TB services in southern Nigeria. Materials and Methods A total of 378 patients accessing TB care were studied using a validated Patient Satisfaction (PS-38) questionnaire on various aspects of TB services. Factor analysis was used to identify eight factors related to TB patient satisfaction. Test of association was used to study the relation between patient satisfaction scores and patient and health facility characteristics, while multilinear regression analysis was used to identify predictors of patient satisfaction. Results Highest satisfaction was reported for adherence counseling and access to care. Patient characteristics were associated with overall satisfaction, registration, adherence counseling, access to care, amenities, and staff attitude, while health system factors were associated with staff attitude, amenities, and health education. Predictors of satisfaction with TB services included gender, educational status, if tested for HIV, distance, payment for TB services, and level and type of health-care facility. Conclusion Patient- and health system-related factors were found to influence patient satisfaction and, hence, should be taken into consideration in TB service programing.